ARBUSCULAR MYCORRHIZAL FUNGI IN CYNODON DACTYLON (L.) PERS. (BERMUDA GRASS) FROM TEMPERATE BLACK SEA COASTAL REGIONS - Palta, Şahin; Palta, Şahin (Parlar Scientific Publications (P S P), 2018)
Arbuscular mycorrhizal fungi (AMF) exist in herbaceous plants' rhizospheres from the Black Sea temperate zone. The AMF is significant for herbaceous plants during their life processes and stages; it has vital importance under the marginal climate conditions and protects plants against soil borne diseases. The aim of this research is to investigate the symbiotic status of AMF species with Cynodon dactylon (L.) PERS., within the temperate coastal regions of the Black Sea. In order to achieve this aim, 20 samples of Bermuda grass were collected from the study area. AMF spore abundance and diversity were determined in the study area during the 2016 dry season. Also, physical and chemical properties of the rhizosphere soils were analyzed, including the pH, CaCO3 content, organic carbon, available P, available K, soil texture, and total N. Furthermore, 12 arbuscular mycorrhyzal fungi species were diagnosed. Identified spores belonged to Ambispora, Dentiscutata, Funnelifornzis, Cetraspora, Claroideoglonius, Acaulospora, Scutellospora, Rhizoglomus, and Gigaspora genus. The diagnosed dominant AMF genus was Gigaspora. The soil of rhizosphere had low organic carbon, low available P, low available K, low total N, high CaCO3 content, almost neutral pH, and sandy soil. The symbiotic status of Cynodon dactylon with arbuscular mycorrhizal fungi species demonstrated that the indigenous Cynodon dactylon carried substantial potential as a host plant for AMF species in sandy soils from Black Sea temperate coastal regions.
Keywords: Arbuscular Mycorrhizal Fungi (Amf); Cynodon Dactylon; Soil Properties; Symbiosis